Spatio-Temporal Processes of Diffusion-Controlled Communication in Hierarchical Multi-Compartments - Qiao, Xin; Chen, Haixu; Schurig, Andreas; Wang, Xiaoliang; Sun, Yinyong; Tobler, Matthias; Boye, Susanne; Castiglione, Kathrin; Appelhans, Dietmar; Huang, Xin (Angewandte Chemie International Edition, 2025)
Exploring the synergy of feedback behavior and molecular communication between micro- and nanocompartments is of great implication for the development of advanced hierarchical living-like materials. Non-covalent interactions are the driving forces for dynamic and temporal events in biomimetic structures. Herein, pH-responsive hierarchical multi-compartments (HMC) are constructed via hydrophobic–hydrophobic interactions between azobenzene units and phospholipid layers through the integration of two distinct structural units: phospholipid-membranized coacervates (Coa@DMPC) and azobenzene-functionalized polymersomes (Azo-Psomes). This enables us to study spatio-temporal signal pathways for biomimetic pH homeostasis and the triggering of feedback-controlled peroxidase-like behavior of Azo-Psomes within HMC. Compared with undocking systems, the information transmission process within HMC shows a high efficiency. Besides the continuous addition of nutrients, the synchronization of two different biomimetic reactions in HMC requires the spatial loading of glucose oxidase and L-phenylalanine ammonia lyase in coacervates and of L-phenylalanine or beta-cyclodextrin/hemin complexes in Azo-Psomes. Azo-Psomes exhibit pH-responsive feedback-controlled behavior. The pH-responsive membrane of Azo-Psomes is responsible for the spatio-temporal peroxidase-like activity of lumen-integrated beta-cyclodextrin/hemin complexes in Azo-Psomes. Finally, this strategy provides a new approach for constructing more complex biomimetic systems by interconnecting at least two membrane-containing compartments to further explore the synergistic mechanisms and feedback behaviors among artificial cell communities.
CRIS-Team Scopus Importer:2025-05-23
Keywords: Azobenzene; Coacervates; Feedback-controlled behavior; Spatio-temporal processes; Phospholipid bilayer; Polymersomes